2018
DOI: 10.24959/ophcj.18.935
|View full text |Cite
|
Sign up to set email alerts
|

The study of the interaction of 4,6-dichloropyrimidine-5-carbaldehyde with glycine esters

Abstract: Вивчення взаємодії 4,6-дихлоропіримідин-5-карбальдегіду з естерами гліцину Мета роботи-дослідження реакції 4,6-дихлоропіримідин-5-карбальдегіду з метил-та трет-бутилгліцинатами з метою виявлення особливостей взаємодії в залежності від умов реакції. Результати та їх обговорення. Встановлено, що реакція 4,6-дихлоро-5-формілпіримідину з гідрохлоридами естерів гліцину в присутності триетиламіну приводить до одержання похідних N-(5-формілпіримідин-4-іл)гліцинату та продуктів циклізації-піроло[2,3-d]піримідину та пі… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…ON-123300 2 (aka.7x), and BI-885578 16. 121,122 Biochemical assays indicated that ON-123300 2 is a strong inhibitor of CDK4 (IC 50 = 3.9 nM) and NUAK1 (IC 50 = 5 nM) and also displays considerable inhibitory activity against FYN (IC 50 = 11 nM), RET (IC 50 = 9.2 nM), FGFR1 (IC 50 = 26 nM), and PDGFRb (IC 50 = 26 nM) (Figure 8). 124 Although tumor development in ON-123300-treated xenograft nude mouse models is inhibited over an 18-day period, mice treated with ON-123300 2 did not exhibit signs of toxicity.…”
Section: Clinical Applications Of Inhibiting Nuak Isoforms and Furthe...mentioning
confidence: 99%
“…ON-123300 2 (aka.7x), and BI-885578 16. 121,122 Biochemical assays indicated that ON-123300 2 is a strong inhibitor of CDK4 (IC 50 = 3.9 nM) and NUAK1 (IC 50 = 5 nM) and also displays considerable inhibitory activity against FYN (IC 50 = 11 nM), RET (IC 50 = 9.2 nM), FGFR1 (IC 50 = 26 nM), and PDGFRb (IC 50 = 26 nM) (Figure 8). 124 Although tumor development in ON-123300-treated xenograft nude mouse models is inhibited over an 18-day period, mice treated with ON-123300 2 did not exhibit signs of toxicity.…”
Section: Clinical Applications Of Inhibiting Nuak Isoforms and Furthe...mentioning
confidence: 99%